2016
DOI: 10.1002/jso.24500
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of patients with hepatocellular carcinoma are determined in multidisciplinary team meetings

Abstract: On an ITT basis, OS was similar whatever the type of curative treatment chosen in MDT. Negative prognostic factors were not following the MDT decision, elevated alpha-fetoprotein, being outside the Milan criteria. J. Surg. Oncol. 2017;115:330-336. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…All this makes the design of prospective trials almost impossible and explains the tremendous selection bias in most of the retrospective analyses in this field. Several studies suggest that up to a third of patients with early HCC end up receiving palliative therapies, rather than undergoing a curative approach as recommended for patients with early disease stages . This might in part be attributed to tumour location, such that patients with “difficult to reach” lesions or those not detectable on ultrasound or CT end up being placed in the palliative treatment group instead.…”
Section: Discussionmentioning
confidence: 91%
“…All this makes the design of prospective trials almost impossible and explains the tremendous selection bias in most of the retrospective analyses in this field. Several studies suggest that up to a third of patients with early HCC end up receiving palliative therapies, rather than undergoing a curative approach as recommended for patients with early disease stages . This might in part be attributed to tumour location, such that patients with “difficult to reach” lesions or those not detectable on ultrasound or CT end up being placed in the palliative treatment group instead.…”
Section: Discussionmentioning
confidence: 91%
“…Although patients in the DMT group had a more favorable stage of disease at time of presentation, the improved OS persisted for BCLC stage 2 to 4 after adjusting for stage. 13 In a 2017 study performed by Charriere et al, 14 improved OS was associated with compliance with the treatment decision made by the DMT. 14 Similar results regarding OS were obtained in a study in a Veterans Affairs system.…”
Section: Discussionmentioning
confidence: 97%
“…MDT management can also shorten the interval from diagnosis to treatment [22], and increase the odds of receiving treatment for HCC [18]. In a cohort study based on data from a MDT meeting dedicated to HCC, non-adherence to the MDT recommendation was one of the negative prognostic factors for OS [20]. MDT management has another advantage as patient is being managed by a group of specialists from multiple fields.…”
Section: Discussionmentioning
confidence: 99%
“…However, MDT with participation by experts from multiple academic disciplines requires additional medical resources and time per patient, which leads to significant healthcare burden and high cost [17]. Several previous studies suggested that MDT management for HCC may improve survival [1824], yet is limited by analyzing small number of patients [1822], comparing patients who were treated in different time period [18,19,22], including those only received MDT management [20,21,23,24], or including those who received curative treatment only [20]. Recently, Serper et al, reported that MDT management was associated with reduced mortality, by analyzing 3,988 patients who received care through the Veterans Administration in involving 128 centers in U.S. [25].…”
Section: Introductionmentioning
confidence: 99%